Broiler Breeder Performance in The Final Phase of Grower - Tetty Barunawati Siagian; Nabilah Khoirunnisa Nugraheni (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2021)
One of the comestibles that have high nutritional value and are easy to obtain is chicken. The higher demand for chicken must be accompanied by an increase in production. It is important for the breeder of broiler chicken to choose high quality Day Old Chick (DOC) from the broiler breeder which also has high quality and productivity. The type of broiler breeder that is grown in PT. Karya Indah Pertiwi is Ross 308. Observations were made when the chickens were 18th to 21st weeks old in 6 henneries totaling about 10,000 chickens. The performance of broiler breeder observed were feed consumption, bodyweight gain, feed conversion ratio, and uniformity. Feed consumption of broiler breeder at 18th to 21st week was 659.4 g/chicken, 700,583 g/chicken, 742,116 g/chicken, 767.2 g/chicken. Bodyweight gain at 18th to 21st week was 143.51 g/chicken, 193.3 g/chicken, 63.43 g/chicken, 167.96 g/chicken. Feed conversion ratio at 18th to 21st week was 4.5, 3.6, 11.6, 4.5. The uniformity at 18th to 21st week was 77%, 81%, 81%, 81%. In conclusion, the value of feed consumption for broiler breeder at PT. Karya Indah Pertiwi was increasing every week. Bodyweight gain at 20th week was lower than 18th, 19th, and 21st week. The value of feed conversion ratio at 20th week was higher than at 18th, 19th, and 21st week. Chicken uniformity value at 18th week was not good it was at 77%, while at the 19th, 20th, and 21st week it was quite good at 81%.